The Impact of Identity Data Administrative Defects on Property Title Certificates and the Mechanism for Restoring Legal Power - Romiz Rizqullah, Fakhri; Hafidz, Jawade (TABELLIUS: Journal of Law, 2025)
This study aims to analyze the role of the Land Office in implementing the principle of prudence in the land registration process and examine the mechanism for correcting identity data to restore the legal force of Land Ownership Certificates (SHM) that are administratively flawed. This research uses a normative juridical approach supported by an empirical case study method. Based on the research, it is concluded that a Certificate of Ownership containing minor administrative defects (differences in birth dates) has the status of a strong, but not absolute, means of proof and does not revoke the land rights. The Repressive (Curative) Role of the National Land Agency is realized through the Certificate Correction or Name Change Registration mechanism according to Article 63 of PP No. 24 of 1997 which is mandatory to restore the legal force of the certificate so that the legal data becomes accurate and up-to-date.